Practices for garment industry’s post-consumer textile waste management in the circular economy context: an analysis on literature - dos Santos, Pedro Seolin (2021)
Goal: This study aimed to identify and describe garment’s post-consumer textile waste management practices and to analyse them according to environmental, economic and social criteria in the circular economy context. Design / Methodology / Approach: A literature review was conducted to identify, collect and organize practices from garment’s post-consumer textile waste management and the environmental, economic and social criteria taken into account for the analysis of such practices in a circular context. Results:  There were eleven collection practices, three sorting practices, five reuse practices, and six recycling practices. Additionally, even circularity is presented as a new solution to environmental problems, those practices identified in literature are pulled mainly downstream, promoting short-term waste management approaches, while the initial production chain’s links continue to extract and use several non-renewable resources from the excessive way. Limitations of the investigation: The limitations of a literature review of this nature is the complete reliance on the defined strings to search the previously published research and the adopted procedures to select and evaluate these studies (data base, search period, exclusion criteria) Practical implications: For researchers and garment’s industry professionals, the identified practices should provide new solutions that could be tested in the current post-consumer textile waste management model. Moreover, this research allowed understanding the way those post-consumer textile waste management’s practices are interpreted under a circular context. Originality/Value: there is almost no detailed study of post-consumer textile waste management’s practices. Furthermore, it is very rare to find those textile waste management practices related in a circular context.